Social Innovation Education in Primary and Secondary Education: An Evaluation - Protopsaltis, Aristidis; Garefi, Ioana; Kalemaki, Irene; Schorer, Antonia (Proceedings of 12th International Social Innovation Research Conference, 2022)
This paper provides an overview of the evaluation results obtained during the second pilot period of the NEMESIS Horizon2020 project. The findings reflect upon the impact of implementing the SIE model of NEMESIS and its components on both students and teachers (and when possible, on other involved stakeholders). The NEMESIS Social Innovation Education (SIE) model consists of three layers, the foundational layer which offers the underlying educational philosophy; the middle layer that provides the design principles used for the structural elements and the top layer offers some context-sensitive program components that allow SIE to be tailored to different local settings and serve for different interpretations of achieved outcomes. The evaluation method used is the realistic evaluation approach. This approach is examining how students were impacted by their involvement in the design, co-creation and implementation of their social innovation projects (Pawson & Tilley, 1997). The evaluation tools used included online surveys for students, teachers, external stakeholders and focus groups with teachers and head teachers. This pilot period included 22 schools in total. Ten (10) schools from the Netherlands however implemented the SIE model through a lesson series and were excluded from the evaluation given that the lesson series approach does not fully appreciated the NEMESIS SIE approach and it has been supplementary of the NEMESIS project that could be followed by prospective schools either as a one-off project or in combination with the SIE model. The data have yielded several key lessons. The most important aspect of NEMESIS was that children felt not only included but in charge of their own projects and this translated directly into increased interest and engagement. Furthermore, the data revealed that is significantly impacting upon improving human relationships among students and helping especially those shy and introvert to step forward and proactively participate in the school life. All in all, student-adult interactions have been very engaging and at the same time very valuable not only for students but also for adults themselves. Apart from supporting the co-creation labs with equipment, the involvement of external stakeholders has been beneficial as they have shared knowledge with the students that the teachers themselves would never be able to do so. Finally, the data has shown that SIE had a positive impact on student’s civic engagement largely as a result of their engagement with social issues and their interaction with external stakeholders, which helped them realise that they can influence change and better understand various social problem
Keywords: Social Innovation Education; Education; Realistic Evaluation